Cerebral sinus venous thromboses in children with acute lymphoblastic leukaemia – a multicentre study from the Nordic Society of Paediatric Haematology and Oncology. (7th October 2014) - Ranta, Susanna; Tuckuviene, Ruta; Mäkipernaa, Anne; Albertsen, Birgitte K.; Frisk, Tony; Tedgård, Ulf; Jónsson, Ólafur G.; Pruunsild, Kaie; Gretenkort Andersson, Nadine; Winther Gunnes, Maria; Saulyte Trakymiene, Sonata; Frandsen, Thomas; et al.
Summary We present a prospective multicentre cohort of 20 children with acute lymphoblastic leukaemia (ALL) and cerebral sinus venous thrombosis (CSVT). The study covers a period of 5 years and comprises 1038 children treated according to the Nordic Society of Paediatric Haematology and Oncology (NOPHO) ALL 2008 protocol. The cumulative incidence of CSVT was 2%. Sixteen of the thromboses were related to asparaginase and 16 to steroids. Most CSVTs occurred in the consolidation phase. Nearly all were treated with low molecular weight heparin without bleeding complications. Mortality related to CSVT directly or indirectly was 10%, emphasizing the importance of this complication.